Fisetin Rescues the Mice Brains Against D-Galactose-Induced Oxidative Stress, Neuroinflammation and Memory Impairment - Ahmad, Sareer; Khan, Amjad; Ali, Waqar; Jo, Myeung Hoon; Park, Junsung; Ikram, Muhammad; Kim, Myeong Ok (Frontiers in Pharmacology, 2021)
Herein, we have evaluated the protective potentials of Fisetin against d-galactose-induced oxidative stress, neuroinflammation, and memory impairment in mice. d-galactose (D-gal) causes neurological impairment by inducing reactive oxygen species (ROS), neuroinflammation, and synaptic dysfunction, whereas fisetin (Fis) is a natural flavonoid having potential antioxidant effects, and has been used against different models of neurodegenerative diseases. Here, the normal mice were injected with D-gal (100 mg/kg/day for 60 days) and fisetin (20 mg/kg/day for 30 days). To elucidate the protective effects of fisetin against d-galactose induced oxidative stress-mediated neuroinflammation, we conducted western blotting, biochemical, behavioral, and immunofluorescence analyses. According to our findings, D-gal induced oxidative stress, neuroinflammation, synaptic dysfunctions, and cognitive impairment. Conversely, Fisetin prevented the D-gal-mediated ROS accumulation, by regulating the endogenous anti-oxidant mechanisms, such as Sirt1/Nrf2 signaling, suppressed the activated p-JNK/NF-kB pathway, and its downstream targets, such as inflammatory cytokines. Hence, our results together with the previous reports suggest that Fisetin may be beneficial in age-related neurological disorders.